The Role of Stereotactic Ablative Body Radiotherapy in Gynaecological Cancers: A Systematic Review. Issue 6 (June 2017) - Mendez, L.C.; Leung, E.; Cheung, P.; Barbera, L.
Abstract: Aims: To summarise and evaluate the current literature in gynaecological tumours treated with stereotactic ablative body radiotherapy (SABR) through a systematic review using the Preferred Reported Items for Systematic Reviews and Meta-analysis (PRISMA) guideline. Materials and methods: A literature search through Medline, EMBASE and Cochrane databases resulted in 22 pertinent manuscripts. Selected studies evaluated the locoregional role of SABR in gynaecological tumours, regardless of SABR clinical indication. Data on local control, toxicity and SABR dose and technique were extracted by at least two investigators. Results: In total, 330 patients received locoregional SABR for gynaecological tumour and had measurable clinical outcomes. Six different clinical scenarios were identified: (i) boost to external beam radiotherapy (EBRT) for cervical cancer as radical treatment; (ii) boost to EBRT for non-operable endometrial cancer; (iii) treatment for pelvic and/or para-aortic node metastases; (iv) adjuvant treatment after surgery in uterine/cervix cancers; (v) salvage of non-nodal pelvic recurrences and (vi) vulvar or vaginal malignancies. Except for SABR as a boost for non-operable endometrial cancer, local control over 80% was found in a range of median follow-up of 4–132 months. Local control in non-operable endometrial tumours receiving SABR was 53%. In salvage treatments for non-nodal pelvic relapses, SABR was associated with about a 20% grade 3–4 gastrointestinal toxicity. Conclusion: There is no clear consensus or evidence on the defined role of SABR in gynaecological tumours. Local control and toxicity associated with SABR seems reasonable for most clinical indications found by this review with a short median follow-up. When used for salvage of non-nodal pelvic recurrences, SABR may be associated with high rates of grade 3–4 late gastrointestinal toxicity. Highlights: SABR was used in six different clinical scenarios. Local control is reasonable, except for definitive management of endometrial tumours. SABR for recurrent pelvic tumours is associated with high toxicity.